An Update on Advancement in Genomics Resources for Spiny Lobster Aquaculture Development - Courtney Lewis; Ahmad Farhadi; Susan Glendinning; Thomas Banks; Tara Kelly; Andrew G. Jeffs; Sandra Infante Villamil; John Breen; Jennifer M. Cobcroft; Arya Vazirzadeh; Basseer M. Codabaccus; Chris G. Carter; et al. (Reviews in Aquaculture, 2026)
The rapid advancement of high‐throughput sequencing technologies has transformed aquaculture genomics, enabling unprecedented insights into the biology and improvement of non‐model aquatic species. Among crustaceans, lobsters represent one of the most commercially valuable yet genomically underexplored taxa. This review synthesises the current state of genomic and transcriptomic resources available for spiny and slipper lobsters (Achelata), contextualising these within the broader decapod framework. We outline key genomic assemblies, transcriptomic atlases, and molecular tools that underpin emerging research on reproduction, nutrition, growth, stress tolerance, and disease resistance. We further highlight how omics‐driven approaches—spanning whole‐genome sequencing, SNP discovery, RNA interference, and nutrigenomics—are reshaping opportunities for selective breeding, reproductive control, and feed optimisation. Recent progress in establishing closed‐cycle aquaculture of Panulirus ornatus now provides the foundation for applying these molecular resources to address key production bottlenecks, including larval duration, cannibalism, and asynchronous moulting. We propose future directions integrating genomics, transcriptomics, and functional tools to accelerate sustainable domestication and genetic improvement of lobsters. Together, these advances mark a pivotal shift toward genomically informed spiny lobster aquaculture.

Preliminary studies of protein and energy requirements for hatchery-reared juvenile slipper lobster (Thenus australiensis) using a factorial model - Andrea Williamson; Chris G. Carter; M. Basseer Codabaccus; Quinn P. Fitzgibbon; Gregory G. Smith (Aquaculture International, 2026)
The slipper lobster ( Thenus australiensis ) is a promising aquaculture species, yet its nutritional requirements remain poorly defined compared to those of other crustaceans. A preliminary factorial model was developed in this study to quantify the daily protein and energy requirements of juvenile slipper lobsters, with demands partitioned into maintenance and growth components. Using data from two controlled growth experiments at 26 °C, regression analyses quantified weight gain as a function of body weight (g BW −1 day −1 ), feed intake, and whole-body composition across juveniles ranging from 5 to 83 g wet weight. Whole-body crude protein (CP) and gross energy (GE) content were stable across size classes, averaging 456 mg CP g BW −1 and 13 kJ GE g BW −1 on a dry-matter basis. Daily maintenance requirements were estimated at 10.8 mg digestible protein (DP) g BW −1 day −1 and 477 J digestible energy (DE) g BW −1 day −1 , with partial utilisation efficiencies of 0.45 for DP and 0.58 for DE. The model predicts shifting DP:DE ratios across instar stages, reflecting increasing maintenance costs with body size. These findings provide a foundation for defining the nutritional needs of juvenile slipper lobsters and deliver applied insights for feed formulation. By expressing requirements as absolute daily demands, the model offers a practical tool for hatchery and grow-out operations, supporting improved feed efficiency and reduced nutrient waste. The next step in validating and refining the model involves expanding research throughout the entire production cycle. Integrating new information and advances in nutritional needs and feed formulation will further enhance the model.

Thermal physiology of tropical rock lobster (Panulirus ornatus); defining physiological constraints to high temperature tolerance - Theodore Uy; Quinn P. Fitzgibbon; Basseer M. Codabaccus; Gregory G. Smith (Aquaculture, 2023)